PENGARUH PENGARUH MEDIA FILM ANIMASI TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI SISWA KELAS VII MTs TANWIRUL ISLAM SAMPANG: PENGARUH MEDIA FILM ANIMASI TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI SISWA KELAS VII MTs TANWIRUL ISLAM SAMPANG - Jihad Salim; Amir Hamzah; Sahrul Muzekki (Lembaga Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Keguruan dan Ilmu Pendidikan PGRI Sampang, Indonesia, 2024)
Education is a conscious, systematic action to create a teaching and learning atmosphere so that students are able to develop their own potential. With education you can build a cavilization that isincreasingly developing day by day. One of the most important thing is education is languange. This research aims to determine the ability of class VII students at MTs Tanwirul Islam Sampang in writing narrative essays and determine the influence of animated film media on students' skills in writing narrative essays. This type of research is quantitative research, while the method used is an experimental method. This research uses a nonprobability sampling technique with a quasi-experimental type of research and use one grub pretest-posttest desaign, with population of 26 students, all of whom were used as samples. The instrument used in this research was a narrative essay writing test. Aspects of class VII pre-test and post-test were processed through a normality test. The results of this research are that animated film media has an influence on the narrative essay writing skills of class VII students at MTs Tanwirul Islam Sampang. This can be seen from the increase in the average score obtained by students, namely obtaining a score of 55.85 on the pre-test using a conventional approach without using media, compared to the average achievement score on the post-test using animated film media in learning, namely obtaining a score of 80,38.